2014
DOI: 10.1073/pnas.1407370111
|View full text |Cite
|
Sign up to set email alerts
|

Functional B-1 progenitor cells are present in the hematopoietic stem cell-deficient embryo and depend onCbfβfor their development

Abstract: Significance All lymphoid cells are considered to be products of hematopoietic stem cells (HSCs); however, it has been suggested, but not proven, that innate immune B-1 progenitor cells develop independently of HSCs in the fetal liver. B-1 cells, especially B-1a cells, are not replaced by adult bone marrow transplantation. Thus, it is critical to understand the origin and mechanisms required to sustain these cells in vivo because B-1 cells play important roles in the first line of defense against mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
88
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(97 citation statements)
references
References 41 publications
7
88
2
Order By: Relevance
“…We (Barber et al, 2011; Montecino-Rodriguez et al, 2006) and others (Esplin et al, 2009; Ghosn et al, 2011; Holodick et al, 2014; Kobayashi et al, 2014; Yoshimoto et al, 2011) have reported that lineage negative (Lin − ) CD93 + CD19 + CD45R(B220) −/low (hereafter CD19 + CD45R −/low ) B-1 specified progenitors are phenotypically distinct from Lin − CD93 + CD19 − CD45R(B220) + CD43 + (hereafter CD19 − CD45R + ) B-2 progenitors (Figure S2). These populations are at a comparable pre-pro-B cell stage, as both have undergone heavy chain D-J, but not V-D-J gene rearrangement (Montecino-Rodriguez et al, 2006), and B-1 progenitors lack V H -D-J H transcripts (de Andres et al, 2002).…”
Section: Resultsmentioning
confidence: 86%
“…We (Barber et al, 2011; Montecino-Rodriguez et al, 2006) and others (Esplin et al, 2009; Ghosn et al, 2011; Holodick et al, 2014; Kobayashi et al, 2014; Yoshimoto et al, 2011) have reported that lineage negative (Lin − ) CD93 + CD19 + CD45R(B220) −/low (hereafter CD19 + CD45R −/low ) B-1 specified progenitors are phenotypically distinct from Lin − CD93 + CD19 − CD45R(B220) + CD43 + (hereafter CD19 − CD45R + ) B-2 progenitors (Figure S2). These populations are at a comparable pre-pro-B cell stage, as both have undergone heavy chain D-J, but not V-D-J gene rearrangement (Montecino-Rodriguez et al, 2006), and B-1 progenitors lack V H -D-J H transcripts (de Andres et al, 2002).…”
Section: Resultsmentioning
confidence: 86%
“…B cell potential independent of HSC formation has been identified in the E9.5 yolk sac coincident with EMP formation (Kobayashi et al, 2014). However, EMPs lack IL7R and Flt3 cell surface markers and Pax5 transcription factor expression, which are associated with lymphoid progenitors arising from HSCs (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In the mouse, HSC-independent hematopoiesis is not only necessary, but sufficient to support the survival until birth of embryos lacking HSCs (Chen et al, 2011). Rare cells with lymphoid potential also arise before adult-transplantable HSCs, including HSC-independent B-1 cell progenitors and immature HSCs capable of becoming HSCs after ex vivo culture or when transplanted into specialized hosts (Arora et al, 2014; Kieusseian et al, 2012; Kobayashi et al, 2014; Yoder et al, 1997). However, the relationship of these cells with EMPs has not been resolved.…”
Section: Introductionmentioning
confidence: 99%
“…Progenitors with B-cell and T-cell potential emerge around E9.0 both in the yolk sac and the embryo proper [9-11, 49]. These lymphoid progenitors migrate to and differentiate in the early fetal liver, and are thought to provide unique subsets of lymphoid cells that persist in the adult, for review see [50].…”
Section: Emergence Of Hematopoiesis In the Fetusmentioning
confidence: 99%
“…Macrophage colony-forming potential is associated temporally and spatially with each of these waves of primitive and definitive erythroid progenitors [4]. Recent cell marking studies have revealed that subsets of tissue-resident blood cells, including some tissue-resident macrophages, do not appear to be replenished by HSCs postnatally, and are instead regenerated by self-renewal of fetal-derived cells [6-11]. In this review, we will consider the developmental origin of fetal-derived macrophages in the context of the various waves of hematopoietic potential that emerge during early embryogenesis.…”
Section: Introductionmentioning
confidence: 99%